Expanded Education Pedagogical References (2018)
This article analyzes some pedagogical references associated with the term expanded education, such as: alternative education, critical pedagogies and emerging pedagogies, in order to specify such terms and explore their relationship with the concept and practices of expanded education. Term similarities and differences are studied and it is concluded that: 1) alternative education directly influences many practices of expanded education; 2) expanded education presents convergence in many aspects with critical pedagogies; and 3), contrary to the prevailing idea that expanded education is an emerging pedagogy, it is shown that it is actually a critical and practical discourse on education, with no normative or prescriptive commitment.